Bacterial extracellular vesicle applications in cancer immunotherapy - Kanika Suri; Anisha D'Souza; Di Huang; Aashray Bhavsar; Mansoor Amiji (Bioactive Materials, 2023)
Cancer therapy is undergoing a paradigm shift toward immunotherapy focusing on various approaches to activate the host immune system. As research to identify appropriate immune cells and activate anti-tumor immunity continues to expand, scientists are looking at microbial sources given their inherent ability to elicit an immune response. Bacterial extracellular vesicles (BEVs) are actively studied to control systemic humoral and cellular immune responses instead of using whole microorganisms or other types of extracellular vesicles (EVs). BEVs also provide the opportunity as versatile drug delivery carriers. Unlike mammalian EVs, BEVs have already made it to the clinic with the meningococcal vaccine (Bexsero®). However, there are still many unanswered questions in the use of BEVs, especially for chronic systemically administered immunotherapies. In this review, we address the opportunities and challenges in the use of BEVs for cancer immunotherapy and provide an outlook towards development of BEV products that can ultimately translate to the clinic.